P33 Improving medicines management in COPD: identifying and addressing sub-optimal treatment. (19th November 2012) - Blackaby, C; Duncan, P; Porter, A
Abstract : Medicines for Chronic Obstructive Pulmonary Disease (COPD) cost the NHS £317m pa. A national improvement programme worked with primary care sites to test practical ways to identify and address potentially sub-optimal prescribing, with a view to improving outcomes and containing cost. Building on learning from initial test sites, selected practises in three CCG areas were supported to analyse primary care data for patients on the COPD disease register and optimise care for these patients. Practises process mapped their current system for managing COPD patients to identify potential improvements. Different methods for data extraction were used to audit diagnosis, disease severity and treatment in relation to NICE guidance. Patients identified as potentially sub optimally treated were called in for review with support of local nurse specialists. Data was collected on respiratory chapter prescribing costs per month per practize, patients reviewed, reasons and outcome. At CCG level, appropriate tools, training and support were developed to help sustain and spread improvement. Early findings from data analysis and patient review identified up to 20% of patients with scope for optimisation of treatment, for reasons including inaccurate diagnosis, poor interpretation of spirometry, and over- or under-treatment in relation to assessment of disease severity. Detailed analysis of patient records required significant input of time and skills, but data extraction tools allowed groups of patients to be targeted more quickly. Review of patients is ongoing. Conclusions: Data analysis and practical support at practise level can identify and address existing problems of misdiagnosis and sub optimal treatment, but are labour intensive and reactive. It is essential to develop a reliable pathway to ensure accurate and timely diagnosis and treatment are maintained for the future. Tools, guidelines, and ongoing education and support can help sustain this. NHS Improvement acknowledges the contribution of project teams from Mansfield and Ashfield CCG, Godiva CCG and University Hospitals Coventry & Warwickshire, & NHS Isle of Wight in this work.